2014
DOI: 10.1016/j.nicl.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth and structural brain alterations in early adulthood

Abstract: Alterations in cortical development and impaired neurodevelopmental outcomes have been described following very preterm (VPT) birth in childhood and adolescence, but only a few studies to date have investigated grey matter (GM) and white matter (WM) maturation in VPT samples in early adult life. Using voxel-based morphometry (VBM) we studied regional GM and WM volumes in 68 VPT-born individuals (mean gestational age 30 weeks) and 43 term-born controls aged 19–20 years, and their association with cognitive outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
164
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 86 publications
(139 reference statements)
15
164
2
1
Order By: Relevance
“…Moreover, very preterm birth is associated with structural brain alterations in early adulthood, whereby volumetric differences in grey matter and white matter are linearly associated with gestational length. [23] It is possible that these persisting anatomical differences lead to an increased risk of stroke in individuals born preterm in our cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, very preterm birth is associated with structural brain alterations in early adulthood, whereby volumetric differences in grey matter and white matter are linearly associated with gestational length. [23] It is possible that these persisting anatomical differences lead to an increased risk of stroke in individuals born preterm in our cohort.…”
Section: Discussionmentioning
confidence: 95%
“…This latter was surprising since the sequelae of hypoxia and other fetal hazards can readily be seen in the brains of nonpsychotic adults who had been born very preterm. 17 In retrospect, it seems that the developmental changes are masked in people with schizophrenia by the effects of antipsychotics and lifestyle factors such as illicit drug abuse on the brain. 18 As exception is abnormal gyrification which remains a marker of aberrant foetal development in schizophrenia and is associated with lack of treatment response.…”
Section: The Origins Of the Neurodevelopmental Hypothesismentioning
confidence: 99%
“…While our analyses demonstrate a relatively specific role of the cBF in premature birth-associated cognitive deficits that last into adulthood, one would not expect cBF volume to be the only factor related to variance in intellectual abilities among VP/VLBW adults. This is also reflected in the mild to moderate effect size of the observed associations between cBF volume and IQ scores (rpart = 0.26 -0.33), indicating that impairments in other cortical and/or subcortical regions and their networking through the brain's white matter may affect intellectual abilities in VP/VLBW adults in at least partially independent ways (12,34,35). In addition, associations between structural/volumetric brain markers and mental capacities are generally indirect in nature and depend on the degree to which the measured structural abnormalities reflect the functional integrity of the neuronal system under study.…”
Section: Resultsmentioning
confidence: 97%
“…However, in our sample of VP/VLBW adults, total WM volume was only marginally reduced compared to controls and was not related to intellectual impairments. While studies on premature birth-associated cerebral abnormalities in adulthood are still rare, two recent volumetric imaging studies on independent cohorts of VP/VLBW adults (34,35) reported very similar observations of more subtle between-group differences compared to the data in infants (31,32) and adolescents (11,29,33). Thus, rather than showing global differences, structural abnormalities in VP/VLBW adults were found to be restricted to specific subcortical GM and WM structures and select cortical limbic and associative regions, indicating that some, but not all, aspects of the adverse effects of premature birth on cerebral structure may normalize during late development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation